Characterization of SdGA, a cold-adapted and salt-tolerant glucoamylase from Saccharophagus degradans - Wayllace, Natael Maximiliano (2021)
Glucoamylases (GAs) are hydrolytic enzymes also known as amyloglucosidases, glucan 1,4-alphaglucosidases or exo-1,4-1,6 bonds) from the non- -Dglucose. These are typically microbial enzymes present in archaea, bacteria and fungi but absent in animals and plants, and they are classified into the GH15 family of glycoside hydrolases (www.cazy.org).-amylases and pullulanases) occurs in the process of saccharification of partially processed starch or dextrins to obtain glucose. Currently, there is strong interest in finding GAs with a better performance at low temperatures because these enzymes would avoid the heating requirement in some industrial processes such as starch saccharification among others, and, in this way, production costs could be minimized. Saccharophagus degradans is a  gramnegative marine bacterium. It is the most versatile bacterium in terms of the degradation of complex polymers (CP) found to date. It is capable to degrade at least 10 complex polymers such as starch, agar, laminarin, cellulose, pectin, alginate, chitin, fucoidan, pectin, pullulan, and xylan at high rate. The objective of this work is to carry out the structural characterization and functional properties of SdGA, a novel glucoamylase (GA) from S. degradans. The enzyme is composed mainly of a N-terminal GH15_N domainlinked to a C-terminal catalytic domain (CD) found in the GH15 family of glycosylhydrolases with an overall structure similar to other bacterial GAs. The protein was successfully expressed in Escherichia coli cells, purified and its biochemical properties were investigated. SdGA showed maximum activity at 39°C and pH 6.0. The enzyme has high activity in a wide range, from low to mild temperatures, like cold-adapted enzymes. It showed the same maximum activity in the range of 0 1.0 M NaCl like salt-tolerant amylases.By thermal inactivation assays, we determined that SdGA is thermolabile at temperatures above 42°C and we found that glycerol 10% (V/V), acarbose 0.1 mM and NaCl 1 M stabilized the enzyme. Furthermore, we analyze the CD of SdGA, other cold-adapted, psychrophilic and thermostable GAs and we found that SdGA has a larger CD due to various amino acid insertions and a higher content of flexible residues compared to other thermostable GAs. These characteristics of SdGA allow it to be classified as a coldadaptedenzyme but also, a salt-tolerant enzyme. We propose that this novel SdGA, might have potential applications for use in different industrial processes that require an efficient alpha glucosidase activity at low/mild temperatures, such as biofuel production.